2016
DOI: 10.3847/0004-637x/818/2/116
|View full text |Cite
|
Sign up to set email alerts
|

The Gould’s Belt Very Large Array Survey. V. The Perseus Region

Abstract: We present multiepoch, large-scale (∼2000 arcmin 2 ), fairly deep (∼16 μJy), high-resolution (∼1″) radio observations of the Perseus star-forming complex obtained with the Karl G. Jansky Very Large Array at frequencies of 4.5 and 7.5 GHz. These observations were mainly focused on the clouds NGC 1333 and IC 348, although we also observed several fields in other parts of the Perseus complex. We detect a total of 206 sources, 42 of which are associated with young stellar objects (YSOs). The radio properties of ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 52 publications
3
31
0
Order By: Relevance
“…Intermediate cases would be assigned the Class I stage. We based our classification on the following criteria: i) near-infrared emission and X-ray emission are usually associated with young stellar objects dominated by a disk (no envelope, e. g., Rivilla et al 2013; Povich et al 2016), and detection in at least one of these signposts, and association with HH objects (no molecular outflows) would suggest a Class I/II nature; ii) if a source is detected in all the signposts of Table 3, with the outflow being molecular, we consider it to be in an intermediate stage (i. e., Class I); iii) sources driving molecular outflows (traced by SiO, CO, or water masers) and being associated with thermal centimeter emission (positive spectral index between 3.6 and 1.3 cm, Zapata et al 2004), with no detection in the infrared or X-rays are typically deeply embedded sources (e. g., Liu et al 2014, Pech et al 2016), suggesting a Class 0/I nature; iv) if a source has not been detected in any of the signposts listed in Table 3, we consider it as deeply embedded (i. e., Class 0/I), since the extreme compact nature of the dust emission suggests that at least an hydrostatic core should have already been formed.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate cases would be assigned the Class I stage. We based our classification on the following criteria: i) near-infrared emission and X-ray emission are usually associated with young stellar objects dominated by a disk (no envelope, e. g., Rivilla et al 2013; Povich et al 2016), and detection in at least one of these signposts, and association with HH objects (no molecular outflows) would suggest a Class I/II nature; ii) if a source is detected in all the signposts of Table 3, with the outflow being molecular, we consider it to be in an intermediate stage (i. e., Class I); iii) sources driving molecular outflows (traced by SiO, CO, or water masers) and being associated with thermal centimeter emission (positive spectral index between 3.6 and 1.3 cm, Zapata et al 2004), with no detection in the infrared or X-rays are typically deeply embedded sources (e. g., Liu et al 2014, Pech et al 2016), suggesting a Class 0/I nature; iv) if a source has not been detected in any of the signposts listed in Table 3, we consider it as deeply embedded (i. e., Class 0/I), since the extreme compact nature of the dust emission suggests that at least an hydrostatic core should have already been formed.…”
Section: Discussionmentioning
confidence: 99%
“…The YSOs emitting gyrosynchrotron emission are typically in the Class II or later stages, and their emission is highly time variable (e.g., Dzib et al 2013Dzib et al , 2015Pech et al 2016). On the other hand, thermal radio jets are non-variable and associated typically with more embedded YSOs (in the Class 0/I stage, e.g., Beltrán et al 2001, Ward-Thompson et al 2011Carrasco-González et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The AMI Consortium: Scaife et al (2011aScaife et al ( , 2011bScaife et al ( , 2012aScaife et al ( , 2012b observed selected protostars in Perseus, Serpens, Taurus, and several isolated cores at low resolution (30″) and sensitivity up to 15 μJy at 1.8 cm. The Gould's Belt Very Large Array (VLA) Survey targeted large sample of protostars in selected star-forming regions with 16 μJy sensitivity and resolution up to 0 4 (Dzib et al 2013(Dzib et al , 2015Kounkel et al 2014;Ortiz-León et al 2015;Pech et al 2016) in C-band (4.1 and 6.4 cm). Reipurth et al (2002Reipurth et al ( , 2004 surveyed a sample of protostars in different star-forming regions with high resolution (0 35) and sensitivity (∼10 μJy) at 3.6 cm and found evidence for a few modestly extended jets.…”
Section: Introductionmentioning
confidence: 99%